2016
DOI: 10.1039/c6ra18530d
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous iron oxide nanowires: synthesis, magnetic and photocatalytic properties

Abstract: Controlled synthesis of mesoporous iron oxide nanowire nanohybrids with enhanced visible light-driven photocatalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Recently, Fe 3 O 4 nanowires were synthesized via high-temperature reduction of α-FeOOH NWs in a fluidized bed reactor [111]. The removal of water molecules and the shearing of the oxide ion planes from AB to ABC stacking during phase transformation from the FeOOH to Fe 3 O 4 make these Fe 3 O 4 NWs porous (Figure 11A,B) [112].…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Fe 3 O 4 nanowires were synthesized via high-temperature reduction of α-FeOOH NWs in a fluidized bed reactor [111]. The removal of water molecules and the shearing of the oxide ion planes from AB to ABC stacking during phase transformation from the FeOOH to Fe 3 O 4 make these Fe 3 O 4 NWs porous (Figure 11A,B) [112].…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
“…While the spherical-shape NPs shows the predictable superparamagnetic blocking behavior, which indicates the role of shape anisotropy on the stoichiometry. It is found that the facets of octahedral particles are consist of the most energetically stable [111] planes and the facets are protected against surface oxidation due to oleylamine coating. Thus, the surface anisotropy is significantly reduced, since the flat surface of the octahedron has fewer broken bonds and oxygen vacancies.…”
Section: Enhancing Inductive Heating By Engineering the Magnetic Nmentioning
confidence: 99%
“…Note that a large surface area does not necessarily imply an improved catalytic performance, as accessibility and surface chemistry are also relevant for catalytic purposes. By extension, nanoarchitectonics have also attracted much attention for heterogeneous catalysis, as an increase in the number of active sites with high accessibility and overcoming the issue of size restriction was encountered with bulk samples (even if these samples are nanoporous) [16][17][18]. The improved catalytic performances are demonstrated in nanostructured catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Nanocrystals with enhanced magnetic properties have been actively pursued for potential biomedical applications such as drug delivery [ 1 , 2 ], hyperthermia therapy [ 3 ], magnetic resonance imaging (MRI) contrast enhancement [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], as well as nanotechnology applications such as catalysis and permanent magnets [ 13 , 14 ]. In order to use these nanoparticles for in vivo or in vitro biomedical applications such as MRI contrast enhancement, the combined properties of high magnetic saturation, stability, biocompatibility, and interactive functions at the surface are essentially required.…”
Section: Introductionmentioning
confidence: 99%